SOSIALISASI ANEMIA PADA REMAJA DI SMA NEGERI 5 PINRANG - Nurlinda Nurlinda; Aisyah Aisyah; Sitti Nabawi; Kharisma Tri Nurindah; Sudarmi Sudirman; Nuralfirah Nuralfirah; Nurjulisah Dudi; Sahir Sahir (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
Anemia is a common health problem among adolescents, especially girls, due to insufficient iron intake required by the body. This community service activity aims to increase adolescents' knowledge about anemia and its prevention efforts through education conducted at SMA Negeri 5 Pinrang. The methods used include activity planning, delivery of educational materials using presentation media, and evaluation through pre-tests and post-tests. A total of 20 twelfth-grade students participated as respondents in this activity. The evaluation results showed a significant improvement in students’ knowledge levels. Before the education session, 10% of respondents were in the poor category, and 90% in the good category. After the session, all respondents showed improvement, with 90% in the excellent category and 10% in the good category. This activity contributes to strengthening health literacy among students and provides an educational-based approach as a promotive-preventive strategy in addressing the problem of anemia in adolescents. Thus, this community service activity not only results in short-term knowledge changes but also provides a foundational contribution to the development of public health education science